Peranan United Nations Joint Program On HIV/AIDS (UNAIDS) Terhadap Penurunan Tingkat Penderita HIV/AIDS Di Zimbabwe - Nurul Anisa Asri; Muhammad Nasir Badu; Pusparida Syahdan (Department of International Relations, Hasanuddin University, 2021)
This study aims to examine the role of UNAIDS in efforts to reduce the rate of HIV / AIDS sufferers in Zimbabwe. The research method used is qualitative with secondary data techniques in the form of books, journals, documents, and various valid sources. All data were analyzed qualitatively. The results of this study indicate that UNAIDS as an international organization has become an aid and channel of foreign aid to Zimbabwe in collaboration with the Zimbabwean government to reduce the level of sufferers in the country. The existence of UNAIDS in Zimbabwe has affected the reduction of HIV / AIDS sufferers. However, this collaborative effort has constraints on Zimbabwe's unfavorable economic and human resource conditions. Apart from that, the cultural factor of society which is quite difficult to accept changes in something is also an obstacle. Penelitian ini bertujuan untuk mengetahui peran UNAIDS dalam upaya penurunan tingkat penderita HIV/AIDS di Zimbabwe. Metode penelitian yang digunakan adalah kualitatif dengan teknik pengumpulan data-data sekunder berupa buku, jurnal, dokumen, dan berbagai sumber valid. Seluruh data dianalisa secara kualitatif. Hasil penelitian ini menunjukkan bahwa UNAIDS sebagai sebuah organisasi internasional menjadi bantuan dan penyalur bantuan luar negeri kepada Zimbabwe bekerja sama dengan pemerintah Zimbabwe untuk mengurangi tingkat penderita di negara tersebut. Keberadaan UNAIDS di Zimbabwe telah mempengaruhi penurunan tingkat penderita HIV/AIDS. Namun, upaya kerjasama ini memiliki hambatan yakni kondisi perekonomian dan sumber daya manusia di Zimbabwe yang kurang baik. Selain itu faktor kebudayaan masyarakat yang cukup sulit menerima perubahan akan suatu hal juga menjadi salah satu hambatan.